2017
DOI: 10.15252/msb.20167416
|View full text |Cite
|
Sign up to set email alerts
|

Engineering bacterial thiosulfate and tetrathionate sensors for detecting gut inflammation

Abstract: There is a groundswell of interest in using genetically engineered sensor bacteria to study gut microbiota pathways, and diagnose or treat associated diseases. Here, we computationally identify the first biological thiosulfate sensor and an improved tetrathionate sensor, both two‐component systems from marine Shewanella species, and validate them in laboratory Escherichia coli. Then, we port these sensors into a gut‐adapted probiotic E. coli strain, and develop a method based upon oral gavage and flow cytometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
210
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(212 citation statements)
references
References 73 publications
2
210
0
Order By: Relevance
“…An emerging focus in synthetic biology engineers microbes to integrate within specific niches in nature, artificial infrastructure and the human body (4)(5)(6)(7)(8)(9)(10)(11). Since genetic programming of bacteria enables them to sense and respond to physiological conditions in situ, this approach is poised to change existing paradigms for diagnosing and treating diseases such as inflammation (12,13), infection (14,15), and cancer (16)(17)(18). An essential element of this approach requires the precise regulation of microbial growth at disease sites, since uncontrolled bacterial replication can lead to severe side effects including tissue damage and septic shock (19,20).…”
mentioning
confidence: 99%
“…An emerging focus in synthetic biology engineers microbes to integrate within specific niches in nature, artificial infrastructure and the human body (4)(5)(6)(7)(8)(9)(10)(11). Since genetic programming of bacteria enables them to sense and respond to physiological conditions in situ, this approach is poised to change existing paradigms for diagnosing and treating diseases such as inflammation (12,13), infection (14,15), and cancer (16)(17)(18). An essential element of this approach requires the precise regulation of microbial growth at disease sites, since uncontrolled bacterial replication can lead to severe side effects including tissue damage and septic shock (19,20).…”
mentioning
confidence: 99%
“…A model chemical (andhydrotetracycline) is used in this study but the design can be adapted to sense biomarkers of interest, including those associated with bacterial infections [48]. Along the same line, another study demonstrated the engineering of a probiotic strain of E. coli (Nissle 1917) to sense thiosulfate and tetrathionate, which are associated with a gut inflammation mouse model infected by Salmonella typhimurium [49,50]. Such whole-cell sensors have the potential of being used for continuous monitoring of host environments for biomarkers associated with bacterial infections.…”
Section: Diagnosis: Identification Detection and Drug Responsementioning
confidence: 99%
“…Recently, researchers from Rice University and Baylor University in Texas took advantage of this idea to engineer a novel strain of bacteria that could report on the intracellular levels of two key metabolites in a mouse model of colitis (1). Even though mounting data show mammalian gut function is regulated through cross-talk between host cells and resident bacteria, deciphering this cross-talk and the signaling molecules involved has proven to be quite a challenge.…”
Section: Sensing a Changementioning
confidence: 99%